Increasing Mu wave desynchronization after dance classes on people with Parkinson’s disease - Vilhalva, Jade Thalia Rodrigues; Imbiriba, Breno Cesar de Oliveira; Krejcova, Lane Viana; Bahia, Carlomagno Pacheco. (Frontiers in Human Neuroscience, 2025)
This pilot study attempted to identify a relationship between dance and mirror neuron activity in people with Parkinson’s disease by investigating Mu rhythm desynchronization in electroencephalographic (EEG) data before and after regular participation in a program of dance classes. During the EEG recordings, the participants observed a sequence of videos showing either choreographic (complex) or daily (simple) movements, each preceded by a baseline image (dark screen) and a control video (moving blocks). The results showed a statistically significant increase in Mu rhythm desynchronization in the alpha 1 band at the central channels after 6 months of dance classes. Control comparisons with occipital channels showed no such increase. Mu rhythm suppression has been demonstrated to reflect the activity of the human mirror neuron system, respond to variations in motor expertise, and seem to be impaired in Parkinson’s disease. The Mu wave desynchronization increase shown here, after 6 months of dance classes, is an objective measurement of the benefits of such practice for people with Parkinson’s disease (PD).